Home-Based Workers and their Ownership in Nepal (Patan Pragya, 2020)
Hom- based workers are the most significant component of informal economy in Nepal. In Nepal, 70percent of the economically active population is involved in the informal economy. Employment in the non-agricultural informal sector is 70 percent of total non-agricultural employment. The employed population in the non-agricultural sectors grew by 29.3 percent. About 30 percent of then on-agricultural workers aged 15 and above are home based workers and home-based work is the major source of employment for women. The share of non-agriculture sector to GDP is highly increasing in recent years; its average annual growth is 7.4 percent in 2018/19. In this study, more than 76 percent of home-based workers are from Tribal/Native/Adibasi ethnicity. Also, the 76 percent home based workers have their own house as ownership. The 86 percent of home-based workers have houses with well window facilities and 99 percent of the houses are facilitated with electricity,41 percent of the households have source of water, 30 percent to hand pump and 6 percent to wells. The 95 percent of home based workers have latrine facilities in their house. The income earned is highly spent on food expenses (54 percent) and remaining is used for other purposes.